Isolation And Characterization of Bacteria from Shallots (Allium cepa L.) as In-vitro Biocontrol Agent of Fusarium oxysporum f.sp cepae - Radiastuti, Nani; Amalia, Wuliani; Suryadi, Yadi; Susilowati, Dwi N; Kosasih, Jajang (Al-Kauniyah: Jurnal Biologi, 2024)
AbstractShallot is one of the leading vegetable commodities with many benefits such as for seasonings and herbal medicinal ingredients. The demand for shallots continues to increase; however, shallot production is still relatively low. One of the limiting factors causing low shallot production is due to wilt disease caused by Fusarium oxysporum f.sp cepae (Foc). Bacteria have many roles in suppressing the growth of Foc, and this study aims to obtain potential bacterial isolates from the shallot plant to inhibit the growth of Foc Based on fungal diameter zone inhibition, degree of inhibition, and chitinase test, it was obtained 9 isolates which could suppress the growth of Foc. The results indicated that the AB3, TB2, and UB1 bacterial isolates could inhibit the growth of Foc with a percentage of inhibition of 46.80; 40.24; and 35.11%, respectively. The analysis showed that AB3, TB2, and UB1 isolates were categorized as moderate in suppressing the growth of Foc. The 16S rRNA sequencing results showed that AB3 and TB2 isolate had similarities with Bacillus subtilis by 99,75%, and 100%, respectively, while UB1 isolate had similarities with Pseudomonas nitroreducens by 89,35%. Based on the result showed that Bacillus sp. AB3 and TB2 isolates, and P. nitroreducens UB1 isolate have more potential as biological control agents to control the Fusarium wilt at in vitro assay. The field efficacy studies on these potential antagonists need to be done in the future.AbstrakSalah satu faktor pembatas yang menyebabkan rendahnya produksi bawang merah adalah penyakit layu yang disebabkan oleh Fusarium oxysporum f.sp cepae (Foc). Bakteri antagonis memiliki banyak peran dalam menekan pertumbuhan Foc, dan penelitian ini bertujuan untuk mendapatkan isolat bakteri antagonis potensial asal tanaman bawang merah untuk menghambat pertumbuhan Foc. Berdasarkan nilai zona hambat diameter jamur, derajat hambat dan uji kitinase, diperoleh 9 isolat yang dapat menekan pertumbuhan Foc. Hasil penelitian menunjukkan bahwa isolat bakteri AB3, TB2, dan UB1 mampu menghambat pertumbuhan Foc dengan persentase penghambatan masing-masing sebesar 46,80; 40,24; dan 35,11% dengan kategori penghambatan pertumbuhan Foc moderat. Hasil sekuensing 16S rRNA, menunjukkan bahwa isolat AB3 dan TB2 memiliki kemiripan dengan Bacillus subtilis masing-masing sebesar 99,75%, dan 100%, sedangkan isolat UB1 memiliki kemiripan dengan Pseudomonas nitroreducens sebesar 89,35%. Berdasarkan hasil penelitian menunjukkan bahwa Bacillus sp. isolat AB3, TB2, dan P.nitroreducens isolat UB1 berpotensi digunakan sebagai agen pengendali hayati untuk mengendalikan penyakit layu Fusarium pada uji in vitro. Studi kemanjuran lapangan terhadap isolat antagonis potensial ini perlu dilakukan di masa depan.